Digital Competence, Talent Management, and Engagement Drive Banking Employee Performance - Abdul Syaban; Asraf Asraf (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the effects of talent management, employee engagement, and digital competence on employee performance at Bank BPD Sultra, a regional development bank in Indonesia. A quantitative cross-sectional design was employed, involving 170 employees selected through purposive sampling. Data were collected using a structured questionnaire and analysed with partial least squares structural equation modelling using SmartPLS 4. The results indicate that talent management, employee engagement, and digital competence each have a positive and significant effect on employee performance. Digital competence produced the strongest effect (β = 0.468, p < 0.001), followed by employee engagement (β = 0.282, p < 0.001) and talent management (β = 0.200, p = 0.005). Together, the three predictors explained 73.7% of the variance in employee performance. These findings show that employee performance in regional banking is increasingly shaped by the ability to use digital systems, manage digital information, communicate through digital platforms, maintain data-security awareness, and solve technology-related work problems. The study contributes to human resource management and digital banking literature by conceptualising employee performance as digitally enabled service performance. Practically, Bank BPD Sultra and similar regional banks should integrate talent development, engagement-enhancing practices, and continuous digital competence training into their human resource strategies. Such integration is essential for improving secure, reliable, adaptive, and customer-oriented banking services in the context of accelerating digital transformation.